1984
DOI: 10.1002/aic.690300402
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of fluidization in a semicircular bed with a jet

Abstract: A hydrodynamic model of fluidization was developed that computes void fractions, pressure and solid and gas velocities in cylindrical fluidized beds. Cmputed time‐averaged gas velocity distributions of a jet compared well with Westinghouse experimental data without the use of any fitted parameters. The main empirical input was a drag correlation from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
2
32
0
2
Order By: Relevance
“…Gidaspow and Ettehadieh [12], Ettehadieh et al [13] and Gidaspow [14] fitted the data to obtain an expression for the emulsion phase elastic modulus. However, numerical computations of Ettehadieh et al [13], Gidaspow [14], Kuipers et al [15] and Bouillard et al [16] have shown that the G(ε) fit obtained from the Rietema and Mutsers [11] data is inadequate in predictive ability. Unrealistically low voidages are predicted with this correlation.…”
Section: Previous Workmentioning
confidence: 99%
“…Gidaspow and Ettehadieh [12], Ettehadieh et al [13] and Gidaspow [14] fitted the data to obtain an expression for the emulsion phase elastic modulus. However, numerical computations of Ettehadieh et al [13], Gidaspow [14], Kuipers et al [15] and Bouillard et al [16] have shown that the G(ε) fit obtained from the Rietema and Mutsers [11] data is inadequate in predictive ability. Unrealistically low voidages are predicted with this correlation.…”
Section: Previous Workmentioning
confidence: 99%
“…In some articles, Gidaspow and his coworkers make it clear that they use the data for glass beads. However, Ettehadieh et al (1984) used two values for G ( E ) that are orders of magnitude apart. Gidaspow (1986) also used a value for G ( E ) that corresponds t o a value for glass beads at a value of void fraction of 0.8.…”
Section: G ( E )mentioning
confidence: 99%
“…In addition to the momentum and continuity equations, closure laws are needed to close the set of equations. The gas and solid friction factors are respectively given by: fg=16Reg1emReg<=21000.0791Reg0.251em2100<Reg<=1051false(2normallnfalse(Regfgfalse)0.8)21emReg>105 and fs=0.0025false|usfalse| where the Reynolds number is defined as: Reg=drfalse|ugfalse|εgρgμgm The modulus of elasticity function adopted for the bubbling bed and riser are respectively given by: G=1010.46εg+6.577 and G=108.76εg+5.43 It is required that the sum of the area phase fractions fulfills the definition: εg+εs=1 The ideal gas law gives the relation between the gas density and gas pressure: ρg=pM…”
Section: Mathematical Modelmentioning
confidence: 99%